2014
DOI: 10.1016/j.ijsu.2014.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the circulatory patho-physiology of anaesthesia – Implications for high-risk surgical patients

Abstract: The paper examines the effects of anaesthesia on circulatory physiology and their implications regarding improvement in perioperative anaesthetic management. Changes to current anaesthetic practice, recommended recently, such as the use of flow monitoring in high risk patients, are already beginning to have an impact in reducing complications but not mortality [1]. Better understanding of the patho-physiology should help improve management even further. Analysis of selected individual clinical trials has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
0
21
0
1
Order By: Relevance
“…We feel that perhaps doing so without fully knowing an individual patient's physiology could potentially lead to increased perioperative complications. This is supported by work done by Wolff et al which suggests that maintaining cardiac output at, or close to, levels as measured prior to induction is likely to be a good reflection of adequate cardiac output and oxygen delivery [13].…”
Section: Resultsmentioning
confidence: 61%
“…We feel that perhaps doing so without fully knowing an individual patient's physiology could potentially lead to increased perioperative complications. This is supported by work done by Wolff et al which suggests that maintaining cardiac output at, or close to, levels as measured prior to induction is likely to be a good reflection of adequate cardiac output and oxygen delivery [13].…”
Section: Resultsmentioning
confidence: 61%
“…(28) This has important implications for surgical fluid management. (22) Excess fluids and Na+ to replace non-existent "third space loss" are not only unnecessary (15) but may actually damage the EGL directly by compression and distortion and also lead to an increase in atrial natriuretic peptide (ANP) which itself damages the layer. The implication is that "third space loss" may actually be precipitated by excess fluids!…”
Section: Factors Regulating Cardiac Outputmentioning
confidence: 99%
“…Experiments using propofol in dogs showed that it produced an increase in venous capacitance due to venodilation (not peripheral arteriolar vasodilation), which we feel a key feature of anaesthesia that has been very little recognised. (18,19) Following venodilation the fall in MAP is due not only to falling preload, SV and CO with a consequent reduction in oxygen delivery (DO2) but also due to a shift of volume out of the arterial tree into the dilated venous compartment. (19) This mimics hypovolaemia.…”
Section: Cardiac Output Changes Fol-lowing Induction and Mainte-nancementioning
confidence: 99%
“…(18,19) Following venodilation the fall in MAP is due not only to falling preload, SV and CO with a consequent reduction in oxygen delivery (DO2) but also due to a shift of volume out of the arterial tree into the dilated venous compartment. (19) This mimics hypovolaemia. The question is whether we should maintain venous capacitance with liberal fluids or by administration of a venoconstrictor?…”
Section: Cardiac Output Changes Fol-lowing Induction and Mainte-nancementioning
confidence: 99%